A Conceptual Framework toward Advanced Aircraft End-of-Life Treatment using Product and Process Features. Issue 3 (2015) - Zahedi, Hamidreza; Mascle, Christian; Baptiste, Pierre
Abstract: The process of treating an aircraft at the end-of-life (EoL) has caused an increasing concern due to the growing number of the manufactured and retired aircrafts each year. While an aircraft EoL maintains a considerable amount of value, it suffers from various environmental and economic issues. In this research, the disassembly process of a real aircraft EoL (Bombardier CRJ-200) has been looked at from a conceptual point of view with an initiative aim to increase the associated added-value while reducing the environmental footprints. It is screened that the overall quality of the recycled materials increases at a reduced demanded effort thanks to a new approach incorporating a set of product and process related features.